ISSUANCE OF DOUBLE CERTIFICATE OF SUPER MARIO BROS BRAND IN THE GENERAL DIRECTORATE OF INTELLECTUAL PROPERTY (Case Study Number 650 K/Pdt.Sus-HKI/2021) - Rogate Oktoberius Halawa; Wiwik Sri Widiarty; Fauzan Fauzan (Sean Institute, 2023)
Business actors must apply for brand registration with a government institution where, in this case, the Directorate General of Intellectual Property Trademarks and Geographical Indications Ministry of Law and Human Rights of the Republic of Indonesia. Such shall be done so that when a product, be it goods or services, is being created and circulated in public will be protected and not claimed by another party. Registered products will have exclusive rights given by the state to the business owners. Furthermore, brands may be applied for more than one party using the same name and categories, creating a double societal brand. Such will result in legal problems and leads to dispute resolution in court. Every judge's decision should be based on the state laws to provide legal certainty for the public as the brands applied for have been through substantive examination. Therefore, for judges to hand down the decision, they should pay attention to the principles of good legislation and considerations used not only because of the well-known brand factors but also the fundamental reasons for the acceptance of the brand itself. Brand applicants are also advised to stick to something other than well-known names that have been prevalent in the public. Instead, they are advised to create and design their own brands that have selling points.